THE EFFECT SIZE OF MINDFULNESS-BASED COGNITIVE THERAPY AS AN INTERVENTION OPTION FOR DEPRESSION - Erlyn Erawan (EXPERIENTIA : Jurnal Psikologi Indonesia, 2012)
Depression as a form of mental health illness is well-known and widespread nowadays in this age and time. Many interventions, curative and preventive, have been created to fight this illness. This paper discussed the use of Jon Kabat-Zinn’s mindfulness meditation and its philosophy when combined with a recognized therapy form, Cognitive Behavioral Therapy, to become Mindfulness-Based Cognitive Therapy (MBCT). Specifically, this paper discussed which aspect of depression that MBCT can specifically tackle when working with depressed individuals, which is their ruminative thinking style. The goal of this paper is to see the effect size of MBCT as an intervention to be used when working with depressed individuals. By looking at the effect size, it can also help to determine how effective this option might be as an intervention.